The Relationship Between the Big Five Personality Traits and the Theory of Planned Behavior in Using Mindfulness Mobile Apps: Cross-sectional Survey - Sunghak Kim; Jin Young Park; Kyungmi Chung (JMIR Publications, 2022)
BackgroundMindfulness has emerged as a promising approach toward improving mental health. Interest in mindfulness mobile app services has also increased in recent years. Understanding the determinants of mindfulness behavior is essential to predict people's utilization of mindfulness mobile apps and beneficial for developing and implementing relevant intervention strategies. Nevertheless, little has been done to determine the predictors of mindfulness behavior. ObjectiveThis study investigates the association between the Big Five personality traits and the Theory of Planned Behavior (TPB) variables in the context of using mindfulness mobile apps to explore the potential indirect effects of conscientiousness and neuroticism on people's behavioral intention for mindfulness, mediated by their attitude toward mindfulness, subjective norm about mindfulness, and perceived behavior control over mindfulness. MethodsThe authors conducted an online, cross-sectional survey in December 2021. Structural equation modeling was conducted to evaluate the overall model fit and test possible linkages among conscientiousness, neuroticism, attitude toward mindfulness, subjective norm about mindfulness, perceived behavior control over mindfulness, and behavioral intention for mindfulness. Bootstrapping mediation analyses were also conducted to test the potential mediating effect in the model. ResultsA total of 297 Korean participants' responses (153 males and 144 females) were analyzed. The proposed model had a good fit. Conscientiousness was correlated with attitude toward mindfulness (β=.384, P<.001), subjective norm about mindfulness (β=.249, P<.001), and perceived behavior control over mindfulness (β=.443, P<.001). Neuroticism was not correlated with attitude toward mindfulness (β=−.072, P=.28), but was correlated with subjective norm about mindfulness (β=.217, P=.003) and perceived behavior control over mindfulness (β=−.235, P<.001). Attitude toward mindfulness (β=.508, P<.001), subjective norm about mindfulness (β=.132, P=.01), and perceived behavior control over mindfulness (β=.540, P<.001) were separately correlated with behavioral intention for mindfulness. Conscientiousness was not directly correlated with behavioral intention for mindfulness (β=−.082, P=.27), whereas neuroticism was directly correlated with behavioral intention for mindfulness (β=.194, P=.001). Conscientiousness was indirectly linked with behavioral intention for mindfulness through attitude toward mindfulness (B=0.171, 95% CI 0.103-0.251) and perceived behavior control over mindfulness (B=0.198, 95% CI 0.132-0.273) but not through subjective norm about mindfulness (B=0.023, 95% CI −0.002 to 0.060). Neuroticism was indirectly linked with behavioral intention for mindfulness via perceived behavior control over mindfulness (B=−0.138, 95% CI −0.197 to −0.088) but not via subjective norm about mindfulness (B=0.021, 95% CI −0.002 to 0.059). ConclusionsThe results show that the integration of the Big Five personality traits and TPB constructs is useful in predicting the use of mindfulness mobile apps. Focusing on conscientiousness and neuroticism in developing information dissemination and implementation strategies for enhancing mindfulness behavior using mobile apps may lead to the successful promotion of mindfulness mobile apps and adherence to mindfulness techniques.